Penguatan Ekonomi Lokal dan Akses Sarana Pertanian Melalui Strategi Pemasaran Lokal untuk Pemberdayaan Masyarakat Desa di Lembang Tondon - Marniati Marniati; Yusuf L. Limbongan; Lantana Dioren Rumpa; Deni Tandisau (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
Strengthening the local economy through better access to agricultural facilities and local marketing strategies is key to empowering rural communities. Lembang Tondon, with its significant agricultural potential, faces challenges such as limited production facilities, fluctuating commodity prices, and reliance on middlemen. This community service program aims to enhance farmers’ capacity by improving access to agricultural inputs and developing marketing strategies. Methods such as surveys, interviews, focus group discussions, and participatory rural appraisal were used to assess the situation and identify opportunities for improvement. Results show that strengthening local institutions, optimizing farmer groups, and implementing direct marketing strategies can boost farmers' income and bargaining power. Collaboration between farmers and stakeholders reduces reliance on intermediaries, creating a more sustainable supply chain. Additionally, training in financial literacy, market analysis, and negotiation skills ensures long-term success. This program supports sustainable rural economic development, food security, poverty reduction, and local resilience, emphasizing the integration of agricultural development with community-driven marketing solutions.